The readability of international illustration of auditor's report: An advanced reflection on the compromise between normative principles and linguistic requirements - Mondher Fakhfakh (Journal of Economics, Finance and Administrative Science, 2015)
The independent auditors periodically publish reports that summarize the audit results. These reports reinforce the financial communication and reliability of accounting information. International Standards on Auditing (ISA) determine the content of audit reports and the quality of audit results. Theoretically, the audit standardization must model intelligible and clear reports for readers. Compliance with linguistic principles contributes to the improvement of the structure of audit reports. In practice, the effectiveness of these reports is criticized because users do not understand the audit information. In order to improve the content of audit reports, International Federation of Accountants (IFAC) had revised International Standards on Auditor's report: ISA 700: Forming an opinion and reporting on financial statements. Linguistically, standardized audit reports could be unreadable by many users of financial statements. This article discusses the linguistic problems related to the preparation of reports. This discussion focuses on the audit reports which are illustrated by the International Standards on Auditing. The results show that in the presence of conflicting requirements (auditing standards versus linguistic principles), independent auditors must optimize the presentation of their reports. – – Los auditores independientes publican periódicamente informes que resumen los resultados de la auditoría. Dichos informes refuerzan la comunicación financiera y la fiabilidad de la información contable. Las Normas Internacionales de Auditoría (NIA) determinan el contenido de los informes de auditoría y la calidad de los resultados. En teoría, la estandarización auditora debe modelar unos informes que sean inteligibles y claros para los lectores. El cumplimiento de los principios lingüísticos contribuye a la mejora de la estructura de los informes de auditoría. En la práctica, se critica la efectividad de dichos informes porque los usuarios no comprenden la información auditora. A fin de mejorar el contenido de estos informes, la Federación Internacional de Contables (IFAC) ha revisado las Normas Internacionales sobre Informes de Auditoría, ISA 700: Establecimiento de una opinión y reporte de informes financieros. Lingüísticamente, los informes de auditoría podrían resultar ilegibles para muchos usuarios de informes financieros. Este artículo trata sobre los problemas lingüísticos relacionados con la elaboración de los mismos. Dicho tratamiento se centra en los informes de auditoría que son ilustrados por las Normas Internacionales sobre Auditoría. Los resultados reflejan que en presencia de requisitos conflictivos (normas de auditoría frente a principios lingüísticos), los auditores independientes deben optimizar la presentación de sus informes.
Keywords: O15; 330; Auditing; International auditors' reports; ISA 700; Content of audits; Understandability; Readability and determinants of legibility; Auditoría; Informes internacionales de auditoría; ISA 700; Contenido de la auditoría; Comprensión; Legibilidad y determinantes de la legibilidad